PENGARUH ATMOSFER TOKO DAN DAYA TARIK INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI TOKO CITRA BUSANA FAAZA COLLECTION BANGIL PASURUAN - Lailatul Hidayati; Laily Muzdalifah (GREENOMIKA, 2021)
The purpose of this study was to determine the effect of store atmosphere and Instagram attractiveness on consumer purchasing decisions at the Citra Busana Faaza Collection store Bangil-Pasuruan. Technique using incidental sampling with a total sample of 97 respondents. This type of research is quantitative research. The analysis tool uses SPSS version 20 program. The data analysis technique was carried out by hypothesis testing, namely partial and simultaneous test. The result of this research that the store atmosphere variable has a positive and significant effect on purchasing decisions. The instagram attractiveness variable has a positive and significant effect on purchasing decisions. Simultaneous test result show that store atmosphere and instagram attractiveness have a significant effect on consumer purchasing decisions.